The Influence of Arabic Gum on the Quality of Instant Ginger (Zingiber officinale Roscoe) - Rahmawati Rahmawati; Giyatmi Giyatmi; E. Marliah (Indonesian Food and Nutrition Progress, 2003)
nstant ginger was traditionally made by crystallizing ginger extract and sugar. The product was easily reconstituted into ginger beverage by dissolution in warm water. The atsiries on this beverage would refresh and warming the body. Unfortunately, the atsiries are unstable during storage. The research is aimed to study the influence of arabic gum on the stability of the product. The method being used was complete random design with two replications. The concentration of the arabic gum was 0, 0.02, 0.04, 0.06 and 0.08%. The parameter being analyzed were moisture content, ash content, total soluble solute, viscosity, and sensory (aroma, color, viscosity, solubility and taste). The result showed that addition ofArabic gum would influence all of the parameters except solubility, color and taste. The best formula was obtained by the addition of 0.04% Arabic gum with the following criteria: ginger strong – ginger stronger aroma, yellowish brown color, slightly viscous, slightly soluble, sweet and slightly warm taste, moisture content 4. SS%, ash content 3.95%, total soluble solute 49.43%and viscosity 21.70 cps. For all criteria the preferences are like moderately.